How Activity-Travel Behaviour Influenced Individuals’ Rate of Accident - Ismail, Muhammad Hamizan (Universiti Teknologi PETRONAS, 2017)
By using five consecutive day time-used activity diary survey and household data from entire Malaysia, this study is to examine the influences between individuals’ activitytravel behaviour and individuals’ rate of accident. From the data, travel behaviour such as number of trips, travel time, and percentage of using certain travel mode of people with high accident rate and low accident rate will be compared to study the differences between them. Generalized Least Square (GLS) method has been chosen as a statistical model to identify what is the most significant variables that influenced individuals’ rate of accident.